MODEL BELAJAR LOMPAT JAUH BERBASIS BERMAIN UNTUK SISWA KELAS V SEKOLAH DASAR - Fandhi, Fandhi; Samsudin, Samsudin; Hernawan, Hernawan; Sujarwo, Sujarwo (Universitas Hamzanwadi, 2025)
This study originated from the problem of low learning outcomes in long jump and monotonous conventional methods. An initial survey in West Bekasi District revealed that 76.54% of students had not achieved the minimum passing criteria, supported by findings that boring learning was the main cause. The purpose of this study was to develop and test the effectiveness of a play-based long jump learning model specifically designed for fifth-grade students. The method used was Research and Development (R&D) with the Borg & Gall model, which included validation by nine experts (athletics, physical education, and play experts), a small-scale trial (25 students), a large-scale trial (45 students), and an effectiveness test with a quasi-experimental design (60 students divided into experimental and control groups). The research results successfully produced 16 structured game models based on the stages of the long jump technique. Expert validation placed the product in the “very good” category (average score of 4.22). The effectiveness test showed a very significant increase in the experimental group with an N-Gain of 76.75% (effective), while the control group only had an increase of 8.13% (ineffective). In conclusion, this play-based long jump learning model has been proven to be very effective, feasible, and can be implemented as an innovative solution to improve the quality of physical education in elementary schools.